ANALISIS PUTUSAN NO: 669/PDT/2016/PT.DKI dan PUTUSAN NO : 3203/K/Pdt/2017 - Gunawan Widjaja; Novi Rizky Ramadhani; Syavitri Ramadhani (Jurnal Salome : Multidisipliner Keilmuan, 2024)
ANALISIS PUTUSAN NO: 669/PDT/2016/PT.DKI dan PUTUSAN NO : 3203/K/Pdt/2017